Role of autoreactive Tc17 cells in the pathogenesis of experimental autoimmune encephalomyelitis - Yong Peng; Xiuli Zhang; Yandan Tang; Shunqing He; Guilan Rao; Quan Chen; Yahui Xue; Hong Jin; Shu Liu; Ziyang Zhou; Yun Xiang (Neuroprotection)
Abstract Background The pathogenesis of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE—an animal model of MS) is primarily mediated by T cells. However, recent studies have only focused on interleukin (IL)‐17‐secreting CD4+ T‐helper cells, also known as Th17 cells. This study aimed to compare Th17 cells and IL‐17‐secreting CD8+ T‐cytotoxic cells (Tc17) in the context of MS/EAE. Methods Female C57BL/6 mice were immunized with myelin oligodendrocyte glycoprotein peptides 35–55 (MOG35–55), pertussis toxin, and complete Freund's adjuvant to establish the EAE animal model. T cells were isolated from the spleen (12–14 days postimmunization). CD4+ and CD8+ T cells were purified using isolation kit and then differentiated into Th17 and Tc17, respectively, using MOG35–55 and IL‐23. The secretion levels of interferon‐γ (IFN‐γ) and IL‐17 were measured via enzyme‐linked immunosorbent assay using cultured CD4+ and CD8+ T cell supernatants. The pathogenicity of Tc17 and Th17 cells was assessed through adoptive transfer (tEAE), with the clinical course assessed using an EAE score (0–5). Hematoxylin and eosin as well as Luxol fast blue staining were used to examine the spinal cord. Purified CD8+ CD3+ and CD4+ CD3+ cells differentiated into Tc17 and Th17 cells, respectively, were stimulated with MOG35–55 peptide for proliferation assays. Results The results showed that Tc17 cells (15,951 ± 1985 vs. 55,709 ± 4196 cpm; p < 0.050) exhibited a weaker response to highest dose (20 μg/mL) MOG35–55 than Th17 cells. However, this response was not dependent on Th17 cells. After the 48 h stimulation, at the highest dose (20 μg/mL) of MOG35–55. Tc17 cells secreted lower levels of IFN‐γ (280.00 ± 15.00 vs. 556.67 ± 15.28 pg/mL, p < 0.050) and IL‐17 (102.67 ± 5.86 pg/mL vs. 288.33 ± 12.58 pg/mL; p < 0.050) than Th17 cells. Similar patterns were observed for IFN‐γ secretion at 96 and 144 h. Furthermore, Tc17 cell‐induced tEAE mice exhibited similar EAE scores to Th17 cell‐induced tEAE mice and also showed similar inflammation and demyelination. Conclusion The degree of pathogenicity of Tc17 cells in EAE is lower than that of Th17 cells. Future investigation on different immune cells and EAE models is warranted to determine the mechanisms underlying MS.